Hardware and software tools for teaching the basics of quantum informatics to lyceums students (Educational Dimension, 2021)
The article defines the criteria for choosing a cloud-oriented platform for mastering the basics of quantum informatics by students of a specialized (high) school: cross-browser; intuitive interface; the possibility of free (free) access; access without registration and simplified registration; the presence of a systematized reference system with examples; support for the development of the environment by the developer; support for working in a personal educational environment; support for working with quantum algorithms in graphical mode; automatic conversion of quantum algorithms from graphic format to program code text; support for the Ukrainian-language locale; availability of a mobile application; responsive design. The possibilities of platforms for implementing quantum algorithms from the following companies are analyzed: Microsoft, QuTech, Amazon Braket, IBM. The choice of the IBM Quantum Cloud-based platform is justified. Work at IBM Quantum Composer and IBM Quantum Lab is described. Information about quantum operations and Gates is presented: their designation in IBM Quantum Composer and IBM Quantum Lab; the gate Matrix; and the purpose of the gate. An example of implementing quantum teleportation in the form of a scheme and program is given.